A reptilian endogenous foamy virus sheds light on the early evolution of retroviruses. Issue 1 (27th February 2019) - Wei, Xiaoman; Chen, Yicong; Duan, Guangqian; Holmes, Edward C; Cui, Jie
Abstract: Endogenous retroviruses (ERVs) represent host genomic 'fossils' of ancient viruses. Foamy viruses, including those that form endogenous copies, provide strong evidence for virus-host co-divergence across the vertebrate phylogeny. Endogenous foamy viruses (EFVs) have previously been discovered in mammals, amphibians, and fish. Here we report a novel endogenous foamy virus, termed ERV-Spuma-Spu, in genome of the tuatara ( Sphenodon punctatus ), an endangered reptile species endemic to New Zealand. Phylogenetic analyses revealed that foamy viruses have likely co-diverged with their hosts over many millions of years. The discovery of ERV-Spuma-Spu fills a major gap in the fossil record of foamy viruses and provides important insights into the early evolution of retroviruses.